Pomiar utraty wartości środków trwałych - Gierusz, Barbara; Martyniuk, Teresa (Measurement of the Depreciation of the Fixed Tangible Assets, 2005)
Tangible fixed assets reduce their value during the period of use and transfer it to products and services. This value transfer may occur due to normal (planned) depreciation or other unpredictable reasons. This article presents situations in which unplanned value reduction may occur and gives an overview of its measurement procedure. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 166-173